Application Of Diversion To Children In Case Of Traffic Accidents That Cause Lives - Dwi Nur Fauziah Ahmad; Handayani Handayani (Jurnal Hukum Replik, 2021)
Minors in driving a motor vehicle are very dangerous, lack of education on road safety and a very early age results in the ability to drive a vehicle not accompanied by instinct and mature thinking so that traffic accidents often occur caused by minors. Law No. 11 of 2012 regulates how to settle cases of child crimes, including in cases of traffic accidents caused by children by diversion. Traffic accident cases regulated in Law No. 22 of 2009 about Traffic and Road Transportation as a law that specifically regulates traffic accidents, the diversion process against children as perpetrators in traffic accidents carried out in every District Court and diversion carried out according to the Act. No. 11 of 2012 and Government Regulation No. 65 of 2012 about Guidelines for the Implementation of Diversion and Handling of Children who are not yet Twelve Years Old. Application of diversion at the Tangerang City Police Station encountered obstacles but there were also efforts to overcome these obstacles.Keywords: children, diversion, traffic